(untitled) (Sustainability in Debate, 2025)
This study analyses socio-environmental vulnerability in Araruama, a municipality in the Lagos São João Hydrographic Region, in Rio de Janeiro, with a history of hydrometeorological disasters and a high number of homeless people. Based on 2010 Census data integrated with the flood susceptibility zone of the SGB and official and media flood records, thematic maps were developed in a GIS environment and crossed with official and media flood records between 2009 and 2023. Twenty-four affected neighbourhoods were identified. The spatialisation of exposure, combined with social vulnerability, enables the identification of the location of the most affected population. Proximity to water bodies was common among the most critical sectors. Areas of extreme socio-environmental vulnerability are located near a river and exhibit low response capacity. The study highlights the need to adopt monitoring and forecasting systems and public policies for the adaptation of the most affected neighbourhoods